Effectiveness of Dynamic Balance Training with and without Visual Feedback on Balance in Ambulatory Stroke Patients - Khushboo C Valodwala; Anjan R Desai (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Stroke is one of the most common neurological disorders leading to chronic disability. Following stroke, patients lose functions of the motor, sensory and higher brain cognitive abilities to various degrees which lead to diminished balance. Balance can be improved with the help of various interventions. Aim: To compare the effectiveness of conventional physiotherapy, wobble board training with and without visual feedback and also check the effectiveness of individual training in ambulatory stroke patients. Materials and Methods: In the present experimental study, total of 51 patients were included; 17 patients per group with Berg Balance Score (BBS) of 41-56, Brunstrom’s recovery stage of 3 or above for the lower limb and Mini Mental Scale Examination (MMSE) score of 24 or more. They were randomly allocated in three groups. Subjects were asked to perform set of exercises for five days a week with total duration of four weeks. Pre and post intervention assessment was carried out by using BBS and Timed Up and Go (TUG). Paired t-test was used within group comparison; ANOVA and post-HOC were applied between the groups. Results: All the three interventions were effective for balance training. All the groups had a significant change for both outcome measures following four weeks of interventions, with p<0.05. The third group showed a significant improvement in balance compared to the two other groups, with p<0.05. The wobble board with visual feedback proved to be significantly effective. Conclusion: This study concludes that all the three interventions are effective, but wobble board training with visual feedback (Sensamove Miniboard) is more effective for balance training than other two interventions.